PERLINDUNGAN HUKUM TERHADAP NASABAH BANK PENGGUNA JASA TRANSAKSI ELEKTRONIK ANJUNGAN TUNAI MANDIRI (ATM) DALAM PRAKTEK DI KABUPATEN BADUNG - Setiawan, Toni; Supasti Darmawan, Ni Ketut; Purwanti, Ni Putu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
Automated Taller Machine (ATM), is one of the banking products to facilitate customers in financial transaction. However, on the other hand the customer as an ATM product user, may experience losses due to damage of the ATM machine. Any utilization of product and services that offered by the bank, the customer have to follow all of the regulation that only determined by the bank. Therefore, this scription will explain about costumer protection as an ATM user, as well as the responsibility of the bank against losses suffered by the customer due to damage to the ATM machine.
Keywords: Automated Taller Machine, Transaction, Costumer Protection, Responsibility